Physical activity and energy expenditure during depressive episodes of major depression - Wielopolski, Jan; Reich, Karin; Clepce, Marion; Fischer, Marie; Sperling, Wolfgang; Kornhuber, Johannes; Thürauf, Norbert (Journal of Affective Disorders, 2015)
Recent data suggest a substantial association between physical activity and depressive symptoms, but there is a lack of research evaluating the physical activity levels in patients suffering from unipolar depression across different stages of disease in an objective way. The aim of the present pilot study was to objectively examine physical activity levels of this patient group compared to healthy controls.Physical activity performance of 19 patients with major depressive episode and 19 healthy controls was assessed at three different time points using a multisensory armband device (SenseWear® Pro3 Armband) and was reported as total energy expenditure (TEE), active energy expenditure (EE), metabolic equivalents (METs), physical activity (PA) and time of lying down (LD), in each case over 24h.Over all measurements, depressive patients presented a significantly lower mean TEE and EE over 24h. Moreover, the patient group showed significantly shorter duration of PA and lower average MET over 24h. When depressive symptoms abated, physical activity parameters significantly increased in the patient group. Correlation analyses demonstrated a significant relation between depressive status/anhedonia and parameters of physical activity, especially in healthy subjects.Results represented valid data for inpatients only.Acute unipolar depression was associated with a significantly lower level of physical activity and showed a significant increase in parallel to clinical improvement. Electronic monitoring of physical activity may be an additional tool for evaluating and controlling therapeutic effects.
EVALuna2:23724